Draft Genome Sequence of Bacillus humi LMG 22167(T) (DSM 16318), an Endospore-Forming Bacterium Isolated from Soil - Wang, Jie-ping (Genome Announc, 2016)
Bacillus humi LMG 22167(T) is a Gram-positive, aerobic, and spore-forming bacterium Here, we report the 4.80-Mb draft genome sequence of B. humi LMG 22167(T), which is the first genome sequence of this species and will promote its fundamental research.